Strategy for Strengthening Women's Entrepreneurship in Efforts to Support Women's Knowledge-Based Food Independence through Banyuasin Regency Cooperative Institutions - Jayanti, Nirmala; Nearti, Yuwinti; Mulyana, Eka (Program Pascasarjana Universitas Sriwijaya, 2025)
This research aims to maximize the potential of women's entrepreneurship through cooperative institutions by supporting food independence, creating a targeted strengthening strategy model that can be adopted and applied not only in cooperative and SME institutions but also to all women entrepreneurs. The research was conducted at the BMT Trans Mekar Sari Mandiri Consumer Cooperative in Mulia Sari Village, Tanjung Lago District. The research involved at least 10% of the total population, namely 100 female entrepreneurial respondents using a sampling technique, namely purposive sampling. The method used in this research is a quantitative method. The data obtained in this research consists of primary and secondary data. Primary data was obtained through direct interviews in the field with sample cooperative members (women entrepreneurs) using a list of questions contained in the form of a questionnaire. Secondary data was obtained from agencies related to this research, namely the Banyuasin Regency Cooperative Service as well as literature such as cooperative RAT reports, books, journals, articles, and previous research. To analyze the data was used SWOT analysis. The results of the research conclude that strategies that can be implemented include maximizing women's abundant resources in cooperatives, carrying out cadres according to standardization, formulating rules for the protection of women in entrepreneurship, making it easier for women entrepreneurs to access capital, and collaborating with various parties supporting the development of women's entrepreneurship.